Iran Diabetes Research Roadmap (IDRR) Study; Gap Analysis of Diabetes Complications in Iran: A Review Article - Zahra ABRISHAMI; Ensieh NASLI-ESFAHANI; Rezvan RAZMANDEH; Baghe LARIJANI; Fatemeh BANDARIAN (Tehran University of Medical Sciences, 2017)
Background: Diabetes mellitus (DM) is a common non-communicable diseases associated with different complications. The study aim was to analyze and report characteristics of research output in the field of diabetes complication in Iran in details and identify research gap in this field. Methods: All scientific diabetes output published by Iranian authors in national and international journals until 2015 was included and analyzed. National and international databases including PubMed, Web of Science, SCOPUS, SID, IranMedex, and Magiran were searched. The obtained results were categorized into eleven subgroups. of complications, comorbidities, management, psychiatry, nutrition, prevention, physical activity, genetics, basic sciences, education and gestational diabetes mellitus (GDM). In each category, documents were classified based on the study design and topic as well as WHO and Australian National Health and Medical Research Council (NHMRC) classification. Results: After screening, 1262 documents remained. Trend of publication was growing during the study period. However, small temporary drop was seen in 2012 and 2014. The most common type of studies in WHO and NHMRC classification belonged to distribution and causes and clinical research, respectively. Cross-sectional and animal designs were the most common methodologies used and vascular complications were the most common subject area in the obtained documents. Conclusion: Subject trend of Iranian studies in the field of diabetes complications is compatible with the prevalence of such complications. However, results show lack of studies with high level of evidence including cohorts and systematic reviews in Iran. Although the trend of publications is growing but considering the importance of this issue, it is not enough and more funds should be allocated in this field. Considering the increasing frequency of basic research close collaboration between basic and clinical research is required to apply these findings in our diabetes guidelines.